Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The trigonometric functions I must know:
(A) $\sin(-x)=-\sin x$
(B) $\cos(-x)=\cos x$
(C) $\cos(x+y)=\cos x\cos y-\sin y\sin x$
(D) $\sin(x+y)=\sin x\cos y+\cos x\sin y$

$\sin^2x+\cos^2x=1$ (Use (C) and $\cos0=1$)

Can anyone help me just understand what the first one is asking. It's giving me a property and I'm supposed to derive the identities. But I don't even know where to begin. Any help? I will post the other problems once I figure this one out.

share|improve this question
    
You have an expression that starts off with $\cos x\cos y$ and you really want an expression involving $\cos^2x$. So you might try setting $y = x$. This doesn't quite work, because in (C) you'll get $\cos 2x$ and not know what to do. But maybe you can tweak this slightly, using (A) and (B)? –  Dylan Moreland Jul 15 '12 at 3:57
    
The paper says I have to use C for number one. Which I honestly do not understand considering there is no $y$ in the problem. –  Austin Broussard Jul 15 '12 at 3:59
    
You will use (C). In (C) you are allowed to plug in different things for $y$. Try setting $y = x$. This will not work, but it will be close to what you want and you should try it for yourself and see why. –  Dylan Moreland Jul 15 '12 at 4:02
    
I will thanks a lot! –  Austin Broussard Jul 15 '12 at 4:03
1  
Here's another approach: The identity you want can be written as $\cos 0 = 1 = \cos z \cos z + \sin z \sin z$. Now do a 'pattern match' on the identities and see what you can set $x$ and $y$ to to get this identity. –  copper.hat Jul 15 '12 at 4:34

3 Answers 3

up vote 2 down vote accepted

Hint: Note that by (A) and (B) $$\cos^2(x)+\sin^2(x)=\cos(x)\cos(-x)-\sin(-x)\sin(x)$$ and apply (C).

share|improve this answer

What you want is to use $(C)$.

$$1=\cos 0 = \cos(x-x)=\cos x \cos (-x)-\sin x \sin(-x)$$

Now you need to use $(A)$ and $(B)$ to obtain the Pythagorean identity.

share|improve this answer
    
I just got back to this problem from after a month has passed but this has been confusing me forever so sorry if my work does not make sense; $$\sin^2(x)+\cos^2(x)=\alpha$$ $$\alpha=\cos(x)\cos(-x)-\sin(-x)\sin(x)$$ $$\cos(x)\cos(-x)=\cos(x-x)\Rightarrow\cos(x)\cos(-x)-\sin(-x)\sin(x)$$ $$\alpha=\cos(x)\cos(-x)\underbrace{-\sin(-x)\sin(x)-\sin(-x)\sin(x)}_{\text{Thi‌​s should equal 0}}$$ $$\alpha=\cos(x)\cos(-x)\Rightarrow \alpha=\cos(x-x)\Rightarrow \alpha=\cos0=1$$ –  Austin Broussard Aug 10 '12 at 6:28

Take y= $cos(x)+isin(x)$

Taking derivative in either side wrt x, $\frac{dy}{dx}=-sin(x)+icos(x)=iy$

Now, integrate $\frac{dy}{y}= idx$

You will find $cos(x)+isin(x)=exp(ix)$+c (c in a undetermined constant).

Put x=0, to find c=0.

So, $cos(x)=\frac{exp(ix)+exp(-ix)}{2}$ and $sin(x)=\frac{exp(ix)-exp(-ix)}{2i}$

Use these two to make the necessary derivation(s).

share|improve this answer
1  
This is not really useful to the OP. –  Pedro Tamaroff Jul 15 '12 at 5:16

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.